Islamic Political Deideology (Policy of the New Order Government in the Application of the Single Principle) - Dedek Sulaiman (Trigin Publisher, 2021)
Deideology means the elimination/abolition of the principles that become the identity and ideological symbols of political organizations and mass organizations, such as the New Order government's policy in politics to weaken communal ideology so that state ideology will no longer be disturbed by the communal ideology. Another target is the receding and weak communal ideology so that Indonesia's future will run well without any ideological conflicts. The strategy of the Old Order government, which was too strongly ideologically and politically oriented, was judged by the New Order regime as having brought political instability and economic destruction that made the people miserable. Therefore, the New Order government felt the need to carry out political stability and security as an important policy that was considered to be able to support the success of the economic development of the New Order regime. This method was then realized in the form of eliminating political ideologies and establishing the principle of Pancasila as a single ideology through the instrument of Law no. 3 of 1985. The aim of this study is to find out the motivation of the New Order government in establishing Pancasila as the sole principle. Knowing the implications of the New Order's political policies in establishing a single principle for Islamic politics.